2020
DOI: 10.3390/su12187474
|View full text |Cite
|
Sign up to set email alerts
|

A Scientometric Review of System Dynamics Applications in Construction Management Research

Abstract: Construction management can be regarded as a complex and dynamic system. In recent years, system dynamics (SD) has been widely applied to solve the complex and dynamic problems in the construction management. However, there is a lack of a scientometric analysis to investigate SD applications in construction management from an objective perspective. To fill out this research gap, this study retrieved a total of 222 relevant articles from the Scopus database. Then, VOSviewer was employed to analyze the collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 81 publications
0
26
0
2
Order By: Relevance
“…The scientometric analysis is a technique that uses mathematical formulas and visualization to discover structural patterns and trace major research boundaries, allowing for a more comprehensive yet concise capture and mapping of scientific knowledge [82,83]. Several authors have used this approach across research areas such as green building [84,85], system dynamics applications [86], building information modeling [87], public-private partnership [88], and sustainability [82,89].…”
Section: Methodsmentioning
confidence: 99%
“…The scientometric analysis is a technique that uses mathematical formulas and visualization to discover structural patterns and trace major research boundaries, allowing for a more comprehensive yet concise capture and mapping of scientific knowledge [82,83]. Several authors have used this approach across research areas such as green building [84,85], system dynamics applications [86], building information modeling [87], public-private partnership [88], and sustainability [82,89].…”
Section: Methodsmentioning
confidence: 99%
“…Based on Park's work, Ansari [28] compared alternative change management policies, including funding, outsourcing activities, schedule adjustments, and labor control by taking into account the time, cost, quality, resources, and financial indicators. An extensive review on schedule changes using the SD model can be found in a previous publication [29]. However, in the SD model, upstream changes are immediately accommodated by changing downstream tasks through feedback loops, without considering a chain reaction of changes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, scientometric analysis is being used by a growing number of scholars to address subjective problems in literature reviews [34][35][36][37]. In contrast, there is a paucity of scientometric analysis in the current studies that explore trends of BIM applications in the PDR projects field.…”
Section: Introductionmentioning
confidence: 99%